Ultrastructure of male genitalia of blow flies (Diptera: Calliphoridae) of forensic importance - Narin Sontigun (2018)
© 2017 Elsevier B.V. Male genitalia of blow flies (Diptera: Calliphoridae) are distinctive in their morphological features and are often used for species identification. The aim of this work was to investigate the male genitalia of blow flies of medical and forensic importance from Thailand at the ultrastructural level, using scanning electron microscopy (SEM). Flies in two subfamilies were examined: Chrysomyinae [Chrysomya bezziana Villeneuve, Chrysomya chani Kurahashi, Chrysomya nigripes Aubertin, Chrysomya pinguis (Walker), Chrysomya rufifacies (Macquart), Chrysomya thanomthini Kurahashi & Tumrasvin, and Chrysomya villeneuvi Patton] and Luciliinae [Hemipyrellia ligurriens (Wiedemann), Hypopygiopsis infumata (Bigot), Hypopygiopsis tumrasvini Kurahashi, Lucilia cuprina (Wiedemann), Lucilia papuensis Macquart, Lucilia porphyrina (Walker), and Lucilia sinensis Aubertin]. Particular attention was paid to the main distinguishing features such as the shapes of the cercus and the surstylus, and the complex structure of the distiphallus. The differentiation of the male genitalia of these species at the SEM level is discussed and compared to the conditions in closely related species such as Chrysomya megacephala (Fabricius). A key for the identification of 14 blow fly species based on male genitalia is provided.